A general framework for estimation and inference of geographically weighted regression models: 2. Spatial association and model specific tests. - Páez, Antonio; Uchida, Takashi; Miyamoto, Kazuaki (Environment & Planning A, 2002)
A development that casts geographically weighted regression (GWR) as a model of locational heterogeneity is presented in order to formulate a general model of spatial effects that includes as special cases GWR with a spatially lagged objective variable and GWR with spatial error autocorrelation. It is indicated that such an approach allows derivation of formal tests against several forms of model misspecification.